100 let Zgodovinskega arhiva Ljubljana - Drnovšek, Marjan (Zgodovinski časopis, 1998)
The celebration of the 100th anniversary of a cultural institution of Ljubljana is an important event for the preservation, editing and publishing of archival sources. Historical Archives of Ljubljana (former Municipal Archives of Ljubljana) has performed an important archival, cultural and historical role since the appointment of the first municipal archivist Anton Aškerc (1898). In the seventies the area of operation of the archives extended over central parts of Slovenia (the area of former province of Carniola). Several notable archivists and historians, among them Vladislav Fabjančič, Jože Šorn, Vlado Valenčič, Božo Otorepec, Sergij Vilfan, Jože Žontar and others, were employed in the archives. The archives put an emphasis on publishing end exhibition of archival sources.
Keywords: archival science; arhivistika; arhivi; Zgodovinski arhiv Ljubljana; zgodovinski pregledi; 100 let